25^ (n-1) + 100= 5^ 2n-1

25^ (n-1) + 100= 5^ 2n-1

given equation is:

let therefore the above equation becomes:

hence

since the base is same compairing the exponents:

  • 7

GOOD QUESTION 

WE CAN WRITE 

5 2(N-1)+100 =5 (2N-1)

2N-2+100 =5 (2N-1)

OR 

2N-1 - 5 2N-2 =100

LET US ASSUME      5 2N-2 =X

2N -1 =====  CAN BE WRITTEN AS = 5X 5 (2N-2) OR 5X

THERE FORE WE HAVE 

5X-X = 100

X = 25

HENCE

2N-2 = 25 = 52

SO 

2N-2 = 2

SOLVEING 

WE HAVE N = 2

  • 3

Please clarify... 

LET US ASSUME 5 2N-2 =X

2N -1 ===== CAN BE WRITTEN AS = 5X 5 ( 2N-2) OR 5X

  • -5
What are you looking for?